An integrated lignocellulose biorefinery process: Two-step sequential treatment with formic acid for efficiently producing ethanol and furfural from corn cobs. (May 2022) - Qiao, Hui; Han, Mingyang; Ouyang, Shuiping; Zheng, Zhaojuan; Ouyang, Jia
Abstract: In lignocellulose biorefineries, the profitability of the process is dependent on efficient feedstock use. To fully valorize all carbohydrates from corn cobs, a newly integrated strategy was developed as a two-step treatment with formic acid for simultaneous production of furfural and ethanol. Corn cobs were first treated with concentrated formic acid at 80 °C for 3 h, and an easily digestible residue with high purity cellulose was fractionated. Following post-treatment, enzymatic hydrolysis, and fermentation, 67.9 g/L ethanol was obtained at 160 g/L initial glucan loading with a high total yield of 75.6%. The fractionated spent liquor was then treated at a high temperature after recovering a large amount of formic acid and lignin by simple rotary evaporation and precipitation. The results showed that the remaining hemicellulose sugar could be converted into furfural using residual formic acid in syrup (31.3 g/L) as a self-catalyst. After optimization of the process, 49.3% furfural yield and 10.8 g/L furfural were achieved at 160 °C for 60 min with the aid of AlCl3 . The two-step approach based on formic acid pretreatment exhibited excellent performance in the efficient conversion of corn cobs into chemicals and energy, which shows enormous potential for biomass refining.